Penemuan Kasus Tuberculosis dengan Menggunakan Metode Pengelola Kasus Tuberculosis ( PEKA TB) - Feri Ekaprasetia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2019)
Tuberculosis incident in Indonesia is very high. The discovery of as many TB suspects as possible will help in the early enforcement of the diagnosis of TB and may soon get treatment. The purpose of this study was to describe suspected TB screening rates using the TB Case Management method (PEKA TB). This study used a descriptive design with 116 samples used. The result was the discovery of suspected TB by using a cadre role showing a finding rate of 58 suspected TB in April and June. Whereas the use of the PEKA TB method for finding TB suspects was 67 Suspects. So that the total suspected findings for 3 months increased from a total of 70 suspected 125 TB suspects. The conclusion of this study is that the use of the PEKA TB method can be an option for finding new cases of tuberculosis patients.